Microstructure and Texture Evolution during Twin-Roll Casting and Annealing of a Mg–6.8Y2.5Zn–0.4Zr Alloy (WZ73) - Kristina Kittner; Madlen Ullmann; Falko Arndt; Rudolf Kawalla; Ulrich Prahl (Crystals, 2020)
In the present work, the microstructure and texture of a Mg–6.8Y–2.5Zn–0.4Zr sheet manufactured by twin-roll casting were investigated. The twin-roll cast state consisted of two apparent phases: the α-Mg matrix, which was made up of dobulites with an average grain size of approximately 50 µm and the LPSO (long-period stacking ordered) phase, which formed network-like precipitates along the grain boundaries. After twin-roll casting, annealing was carried out under conditions of different temperatures ranging from 450 °C to 525 °C and holding times between 2 h and 24 h. It was found that heat treatment led to the formation of a microstructure in which grains were apparent. Furthermore, it could be observed that high temperatures > 500 °C led to changes in the morphology of the LPSO structures. On one hand, the network-like structure dissolved while, on the other hand, both rodlike and blocky LPSO phases precipitated predominantly at the grain boundaries of the α-Mg matrix. This process was fostered by high temperatures and long holding times.